CONTEXTUALIZING INDIVIDUAL TAXPAYERS' READINESS TO MOVE ON (FROM USING PRESUMPTIVE TAX FACILITY) - Silkapianis, Asya Annisa; Khoirunnisa, Indah Rosewika Suryaning; Qadri, Resi Ariyasa (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract” The tax mechanism known as turnover-based presumptive tax is provided to taxpayers operating within the micro, small, and medium sectors. Presumptive tax, in principle, is exclusively imposed for a specific duration. Individual taxpayers will transition back to the conventional taxation method in 2025. This study aims to explore the factors that influence the willingness of individual taxpayers to transition from utilizing the presumptive tax facility to adopting the conventional taxation scheme. The present study used a qualitative methodology, explicitly employing a case study framework within the context of South Tangerang. We collected primary data through interviews and obtained secondary data from literature documentation. We analyzed the gathered data using thematic and triangulation analysis methods. This research found six factors that influence the willingness of individual taxpayers to adopt changes in the taxation system. This paper makes a valuable contribution to the government by offering an overview of the critical factors that require attention to enhance individual taxpayers' readiness for the shift in their taxation mechanism. Keywords: Determinant; MSME; Presumptive; Readiness; Tax